Pendidikan Islam Berbasis Multi Intelejensi: Upaya Mengintegrasikan Konsep Kecerdasan Majemuk dalam Pengajaran Nilai-Nilai Islam - Mutmainnah Hamid; Wardana Wardana; Aminullah Aminullah (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to explain and analyze the application of the theory of multiple intelligences in the context of Islamic Religious Education (PAI). The theory of multiple intelligences proposed by Howard Gardner offers an educational approach that recognizes the diversity of potential intelligences within humans. This approach is very much in line with the basic principles of Islamic teachings that emphasize the holistic development of human potential: intellectual, emotional, spiritual, and social. The method used is library research, by reviewing relevant primary and secondary literature. The results of the study indicate that the integration of the concept of multiple intelligences into Islamic Religious Education can strengthen the effectiveness of learning and strengthen the character of students.